U.S. News Spillover Effects: Sectoral Evidence - Nguyen, Anh Tho Thi (2011)
This paper is a study of the spillover effects of U.S. macroeconomic news on different sectors of the Australian stock market. We find that an indication of economic contraction from the United States raises the conditional mean, and most news elicits associated volatility in the Australian stock market. We further document that different sectors respond differently to U.S. news. For example, U.S. news has the strongest effect on the first two moments of the Australian Industrials and Property Trusts stock returns and the least impact on the Materials sector. Furthermore, we document that while U.S. news has been absorbed relatively quickly on the conditional mean, the volatility impact is somewhat persistent.